The role of Frizzled-4 mutations in familial exudative vitreoretinopathy and Coats disease. Issue 4 (21st November 2010) - Robitaille, Johane M; Zheng, Binyou; Wallace, Karin; Beis, M Jill; Tatlidil, Cuneyt; Yang, Jenny; Sheidow, Tom G; Siebert, Lee; Levin, Alex V; Lam, Wai-Ching; Arthur, Brian W; Lyons, Christopher J; et al.
Abstract : Aim: The aim of this study is to assess the role of Frizzled-4 ( FZD4 ) in familial exudative vitreoretinopathy (FEVR) and Coats disease. Methods: Tissue samples were collected for DNA extraction and automated DNA sequencing of the two coding exons of FZD4 in both directions. Cases carrying a FZD4 mutation and demonstrating extreme disease severity were selected for direct automated sequencing of all coding exons of LRP5, NDP and TSPAN12 . Clinical data were obtained for the purpose of identifying genotype–phenotype correlations. Results: 68 probands were diagnosed as having autosomal dominant or sporadic FEVR. Eleven FZD4 mutations (five missense, three deletions, one insertion, two nonsense) were identified. Six of these mutations are novel, and none were found in 346 control chromosomes. In 16 cases of Coats disease, one polymorphism combination was found in two samples: no mutations were detected. No genotype–phenotype correlation emerged. Three severely affected cases with FZD4 mutations failed to show additional mutations in the three other FEVR genes. Conclusion: The authors identified 12 FEVR probands with FZD4 mutations. FZD4 mutation screening can be a useful tool especially in mild or atypical cases of FEVR. Germ-line mutations in FZD4 do not appear to be a common cause of Coats disease.